The function of memory in understanding and addressing cultures in impunity - Jereza, Veronica (2016)
Recent psychological studies show that systemic oppression may be understood as trauma, which is aggravated in the context of a culture of impunity. Cultures of impunity, then, are a problem not only of legal justice and collective trauma but also of personal memory and its fragmentation. Following developments in trauma studies and Paul Ricoeur's Memory, History, Forgetting and Lectures on Ideology and Utopia, cultures of impunity may be understood as an institutionalized forced forgetfulness with destructive and self-reinforcing effects on personal and collective memory.
Keywords: Memory; Trauma; Impunity